2014
DOI: 10.1128/jb.02217-14
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen in Myxococcus xanthus Identifies Mutants That Uncouple Outer Membrane Exchange from a Downstream Cellular Response

Abstract: Upon physical contact with sibling cells, myxobacteria transiently fuse their outer membranes (OMs) and exchange OM proteins and lipids. From previous work, TraA and TraB were identified to be essential factors for OM exchange (OME) in donor and recipient cells. To define the genetic complexity of OME, we carried out a comprehensive forward genetic screen. The screen was based on the observation that Myxococcus xanthus nonmotile cells, by a Tra-dependent mechanism, block swarm expansion of motile cells when mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 44 publications
5
42
1
Order By: Relevance
“…To track the fate of such cells, time-lapse microscopy was used 24 h after the cell mixture was plated. As previously reported (2,14), many of the cells at the swarm edge moved slowly or not at all (compare Movies S1 and S2 in the supplemental material), suggesting that those cells were sick or dead. In addition, in two cases, isolated cells lysed (see Movie S1).…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…To track the fate of such cells, time-lapse microscopy was used 24 h after the cell mixture was plated. As previously reported (2,14), many of the cells at the swarm edge moved slowly or not at all (compare Movies S1 and S2 in the supplemental material), suggesting that those cells were sick or dead. In addition, in two cases, isolated cells lysed (see Movie S1).…”
Section: Resultssupporting
confidence: 50%
“…We previously showed that swarm inhibition is Tra dependent (Fig. 1A) (2,14). That is, when either strain in the mixture contains a traA or traB mutation, swarm inhibition is abolished.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although myxobacteria have a peculiar ability to produce long filamentous OM tubes, which some have argued are conduits for exchange, we find no evidence that these structures are required for OM exchange (23). Instead, we suggest that TraAB, the only known determinants for OME (50), catalyze the formation of prefusion junctions that lead to OM fusion and exchange.…”
Section: Discussioncontrasting
confidence: 38%
“…OME requires the production of an outer membrane protein complex, TraAB, in both the donor and recipient cell (126). TraAB appears to be the only component necessary to mediate OME (128) and, similarly to the BamA receptor in CDI systems, TraAB contains a polymorphic domain that limits OME to a narrow range of related targets (129). Given the functional similarities to CDI systems and the potential of OME to directly deliver toxic effectors into the envelope of target bacteria, it is not surprising that Myxobacteria use OME to mediate competition and engage in kin recognition.…”
Section: Contact-mediated Competitionmentioning
confidence: 99%